Formulation Development and Characterisation of Perfluorocarbon Nanobubbles for Sorafenib Delivery - Subramanian Selvamuthukumar (Journal of Global Pharma Technology, 2019)
Nanobubbles (NBs) are novel drug delivery systems with combination of ultrasound contrast agents and drug carrier that could potentially act at specific target sites. Sorafenib is an anticancer drug for the treatment of hepatocellular carcinoma. In this study, sorafenib loaded nanobubbles were prepared by the thin film hydration method. Morphology was examined by Scanning electron microscopy and Atomic force microscope. Particle size and Zeta potential were determined by laser- scattering method. Ultrasound imaging was performed on a digital ultrasonic imaging system. The drug content in the sorafenib loaded NBs was determined by using HPLC method. The in vitro release profile of sorafenib loaded NBs was determined using a Franz diffusion cell method with absence and presence of Ultrasound exposure. The sorafenib NBs expected a spherical shape with a uniform particle size (170 nm), negative zeta potential (-52.47 mV) and polydispersity index (0.289). Ultrasound imaging confirmed the acoustical activity of perfluoropropane nanobubbles. Drug content was found to be 96 %. A slow and prolonged spontaneous drug release was observed in vitro, which was enhanced upon ultrasound stimulation. This result suggests that sorafenib loaded NBs can be considered a novel chemotherapeutic approach for treating liver cancer in combination with an ultrasound contrast agents.Keyword: Nanobubbles, Sorafenib, Perfluorocarbon, Ultrasound, Hepatocellular carcinoma